Nanoparticles with multiple properties for biomedical applications: A strategic guide. Issue 4 (August 2016) - De Crozals, Gabriel; Bonnet, Romaric; Farre, Carole; Chaix, Carole
Graphical abstract: Highlights: The great potential of multifunctional nanoparticles in diagnostics and medicine is presented. Common methods of functionalization such as core-shell formation and surface chemistry are discussed. Recent strategies like formation of nanoassemblies and asymmetrization are highlighted. Solid-phase strategies are promising to combine multiple functionalities at the nanoscale. Abstract: The technology to develop nanosized particles offering multiple properties carries tremendous potential for the development of applications in nanomedicine. Nanoparticles providing multimodal detection and/or multifunctionality could be of great interest in imaging applications, targeting, therapy and in vitro diagnostics. The precise control of surface chemistry is particularly important when nanomaterials are brought to interact with biology. Despite recent progress, the multifunctionalization of nanosized objects is still a major challenge for chemists. Here, we propose an overview of nanoparticle functionalization strategies, emphasizing those that permit the incorporation of multiple functions and/or biomolecules on the surface. This review is a general guide to help scientists to design nanoparticles tailored for specific biomedical applications. Multifunctional nanomaterials, ranging from core/shell structures to Janus nanoparticles, are explored and related chemistries are commented. The most promising and preferred materials are listed in relation to their applications and the main surface functionalization strategies are compared. New trends in multifunctionalization using solid-phase methods are also detailed.